2020
DOI: 10.1002/ana.25927
|View full text |Cite
|
Sign up to set email alerts
|

Role of B Cells in Multiple Sclerosis and Related Disorders

Abstract: The success of clinical trials of selective B‐cell depletion in patients with relapsing multiple sclerosis (MS) and primary progressive MS has led to a conceptual shift in the understanding of MS pathogenesis, away from the classical model in which T cells were the sole central actors and toward a more complex paradigm with B cells having an essential role in both the inflammatory and neurodegenerative components of the disease process. The role of B cells in MS was selected as the topic of the 27th Annual Mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 102 publications
(102 reference statements)
2
111
1
3
Order By: Relevance
“…The significant effects of anti-CD20 mAbs on relapses may be partly explained by the ability of these medications to suspend a subset of B lymphocytes which are pathogenic in MS patients. Indeed, B cells are potent antigen presenting cells which mediate T cell activation, and they can also produce pathogenic antibodies ( Comi et al, 2020 ). Moreover, a subset of B cells are active producers of cytokines that regulate the proinflammatory (interleukin [IL]−6) as well as the anti-inflammatory responses (IL-10) ( Lehmann-Horn et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significant effects of anti-CD20 mAbs on relapses may be partly explained by the ability of these medications to suspend a subset of B lymphocytes which are pathogenic in MS patients. Indeed, B cells are potent antigen presenting cells which mediate T cell activation, and they can also produce pathogenic antibodies ( Comi et al, 2020 ). Moreover, a subset of B cells are active producers of cytokines that regulate the proinflammatory (interleukin [IL]−6) as well as the anti-inflammatory responses (IL-10) ( Lehmann-Horn et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms underpinning the efficacy of CD20 cell depletion in MS and its animal models remain incompletely understood. 47 , 50 55 The interaction of specifically B and T cells may be particularly relevant to MS pathology. 56 The effectiveness of B-cell depletion in MS has been invoked to support the hypothesis that B cells latently infected with Epstein-Barr virus may play an important role in the pathogenesis of MS. 57 , 58 Animal studies have indicated that CD20 depletion modulates activation of monocytes and microglia and the recruitment of T lymphocytes.…”
Section: Msmentioning
confidence: 99%
“… 35 However, it remains difficult to explain how B- cells’ accumulation as part of CNS-compartmentalized inflammation, may be limited by therapies as anti-CD20 antibodies that do not cross the blood–brain barrier (BBB). 36 …”
Section: B-cells In Ms: Implications For Clinical Use Of Anti-cd20 Mabsmentioning
confidence: 99%